The Influence of EU Membership on Country's Competitiveness - The Case of Estonia - Bochańczyk-Kupka, Dominika (Publishing House of the Wrocław University of Economics, 2009)
The international country’s competitiveness is one of the most interesting issues of modern economics. It can be defined and measured by many different ways and in modern literature we can find plenty of articles and books which try to describe this economic category. This article is dedicated to Estonia so it focuses mainly on macroeconomic level of international competitiveness. The main aim is to describe how the Estonia’s membership in European Union has influenced its international competitive position using measures such as: Global Competitiveness Index made by WEF, World Competitiveness Index created by IMD and measures of Lisbon Strategy implementation (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 57-66